Quality of primary care practice in a large HMO according to physician specialty. - Grumbach, K (1999)
OBJECTIVE: To determine whether physician specialty was associated with differences in the quality of primary care practice and patient satisfaction in a large, group model HMO. DATA SOURCES/STUDY SETTING: 10,608 patients ages 35-85 years, selected using stratified probability sampling from the primary care panels of 60 family physicians (FPs), 245 general internists (GIMs), and 55 subspecialty internists (SIMs) at 13 facilities in the Kaiser Permanente Medical Care Program of Northern California. Patients were surveyed in 1995. STUDY DESIGN: A cross-sectional patient survey measured patient reports of physician performance on primary care measures of coordination, comprehensiveness, and accessibility of care, preventive care procedures, and health promotion. Additional items measured patient satisfaction and health values and beliefs. PRINCIPAL FINDINGS: Patients were remarkably similar across physician specialty groups in their health values and beliefs, ratings of the quality of primary care, and satisfaction. Patients rated GIMs higher than FPs on coordination (adjusted mean scores 68.0 and 58.4 respectively, p<.001) and slightly higher on accessibility and prevention; GIMs were rated more highly than SIMs on comprehensiveness (adjusted mean scores 76.4 and 73.8, p<.01). There were no significant differences between specialty groups on a variety of measures of patient satisfaction. CONCLUSIONS: Few differences in the quality of primary care were observed by physician specialty in the setting of a large, well-established group model HMO. These similarities may result from the direct influence of practice setting on physician behavior and organization of care or, indirectly, through the types of physicians attracted to a well-established group model HMO. In some settings, practice organization may have more influence than physician specialty on the delivery of primary care.